The interplay between lying, sitting, standing, moving, and walking on obesity risk in older adults: a compositional and isotemporal substitution analysis - Jana Pelclová; Jan Vindiš; Paulína Jašková; Karel Hron (BMC Geriatrics)
Abstract Introduction Obesity in older adults is linked to various chronic conditions and decreased quality of life. Traditional physical activity guidelines often overlook the specific postures and movements that older adults engage in daily. This study aims to explore the compositional associations between posture-specific behaviours and obesity risk in younger (M = 67.35 ± 2.03 years) and older (M = 75.73 ± 4.17 years) groups of older adults and investigate the differences in body mass index (BMI) associated with replacing time spent in lying, sitting and standing with moving or walking. Methods This cross-sectional study involved 309 older adults aged 65 and above from Czech Republic. Participants’ movement behaviours, including lying, sitting, standing, moving, and walking, were measured using accelerometers. The data were analysed using compositional data analysis (CoDA) and isotemporal substitution models to assess the impact of reallocating time between different activities on self-reported (BMI). Results The younger group engaged in more overall movement (193.84 min/day vs. 172.41 min/day) and walking (92.15 min/day vs. 76.62 min/day) than the older group. Significant estimated increases in BMI were associated with reallocating 30 min from movement to lying, sitting, or standing (up to + 3.31 kg/m²), while reallocating the same amount of time from lying, sitting, or standing to movement was associated with estimated reductions in BMI (up to − 2.54 kg/m²). In the older group, reallocating time from slow walking to lying or sitting was associated with estimated increases in BMI (up to + 1.86 kg/m²), while increasing time spent slow walking at the expense of lying or sitting theoretically reduced BMI (up to − 0.95 kg/m²). Conclusions The findings suggest that promoting movement and walking, including both slow and fast walking, may play a role in managing obesity risk in older adults. This study highlights the potential benefits of reducing sedentary time and encouraging low-intensity physical activity tailored to the capabilities of seniors, especially those aged 70+, as a possible strategy to mitigate obesity risk. However, further longitudinal studies are needed to confirm these associations and explore causal relationships.